Elastic fracture mechanics analysis of bi-materials using boundary element method - Tay, Denzil Song Heng (Nanyang Technological University, 2022)
An analysis of an elliptical hole inclusion between the two materials is done, along with the relation between an interface crack in between two isotropic elastic half palates that are dissimilar. Only tensile loads operating perpendicular to the crack axis and acting on the matrix are considered. For a variety of reasons, Stress Intensity Factors (SIF) are found in elastic combinations of the two-step model. The present technique employs quadratic quarter-point crack-tip element that is also known as Quarter Node Shift (QNS) and is based on its multi-region boundary element method (BEM). Depending on the relative elastic properties of the matrices, orientation, and distance of the hole inclusion from the crack tip, the interaction of the elliptical hole inclusion may cause propagating or shielding effects on the SIF of the crack tip.